Hand hygiene in emergency care: cross-sectional study on adherence and behavior of the team - Alvim, Andre Luiz Silva; Araújo, Cristiane; Silva , Claudilene Fernandes da; Araújo, Camila Ribeiro; Paulino, Yuri Neves Arantes; Dutra, Herica Silva; Faria, Luciane Ribeiro de; Batista, Odinéa Maria Amorim (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Healthcare professionals working in emergency care perform hand hygiene on few occasions when in contact with the patient and/or nearby areas. Aim: To verify adherence and behavior of healthcare professionals regarding hand hygiene practices in emergency care. Outlining: Cross-sectional, descriptive, quantitative study conducted with 39 healthcare professionals working in emergency care. Data were analyzed using descriptive statistics and multiple linear regression. Results: A total of 230 observations were made during day and night shifts. The majority did not use adornments during their workday (81.0%). The adherence rate was 33.0%, with the lowest frequency before performing aseptic procedures (24.0%) and before contacting the patient (27.1%). Nurses stood out among the evaluated professionals (39.5%). There was no statistical difference between the products used for handhygiene and the adherence rate (p=0.20). Implications: It is necessary to implement strategies to sensitize healthcare professionals about hand hygiene, as the participants' performance was low.